2021
DOI: 10.1111/ans.17071
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on colorectal cancer diagnosis and management: a Binational Colorectal Cancer Audit study

Abstract: Not based on previous communication to a society or meeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 10 publications
(14 reference statements)
6
49
0
Order By: Relevance
“…There was also a troubling trend seen in the final pathology of the CRC diagnosed during the ramp up period with more advanced stages and more metastatic cancer was identified when compared to the same period in 2019. A similar finding of more advanced CRC at diagnosis was also seen in Australia and New Zealand, where the post-lockdown period saw an increase in urgent or emergency procedures for colorectal cancer, more stoma creation, and a proportionally higher rise in Stage II or III disease and decrease in stage I disease [ 23 ].…”
Section: Discussionmentioning
confidence: 59%
“…There was also a troubling trend seen in the final pathology of the CRC diagnosed during the ramp up period with more advanced stages and more metastatic cancer was identified when compared to the same period in 2019. A similar finding of more advanced CRC at diagnosis was also seen in Australia and New Zealand, where the post-lockdown period saw an increase in urgent or emergency procedures for colorectal cancer, more stoma creation, and a proportionally higher rise in Stage II or III disease and decrease in stage I disease [ 23 ].…”
Section: Discussionmentioning
confidence: 59%
“…Our results showed that the rate of elective primary tumor resections reached around 70% over time and did not decrease after 2020. A study in Australia and New Zealand and a single‐site Japanese study found a significantly larger share of urgent CRC cases during the pandemic 31,39 . The different definitions of “urgent” or “emergency” cases used between studies do not allow direct comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Single site studies in Romania and Brazil and a larger studies in France, Australia and New Zealand found significantly more advanced new CRC cases after the pandemic broke out, but a single‐site South‐Korean study found no statistically significant difference in pTNM stage distribution after Covid19. 13 , 14 , 16 , 30 , 31 Single‐site studies cannot exclude the fact that patients could have gone to another provider for treatment, whereas our study includes the AP‐HP teaching hospitals in Paris region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If gastrointestinal malignancy case detection rates drop, such as has likely occurred in the COVID-19 pandemic, GN-BSI as a marker of occult gastrointestinal malignancy should be considered. (Søgaard et al, 2017;Williams et al, 2021) During the acute period following index blood culture collection, urinary tract infection and sepsis were common UCOD in patients with GN-BSI. Beyond 90 days, infection was not a common UCOD in the following years for either group.…”
Section: Discussionmentioning
confidence: 99%